Periarticular osteopenia in adjuvant induced arthritis: role of interleukin-1 in decreased osteogenic and increased resorptive potential of bone marrow cells. Issue 6 (June 1995) - Suzuki, Y; Tanihara, M; Ichikawa, Y; Osanai, A; Nakagawa, M; Ide, M; Mizushima, Y
Abstract : OBJECTIVE–To clarify the local osteogenic and bone resorptive potential of periarticular bone in adjuvant induced arthritis (AIA). METHODS–Formation of fibroblast colony forming units (FCFU; osteogenic precursor cells) and osteoclast-like cells in bone marrow culture was studied in AIA rats. Osteoclast-inducing activity in the AIA rat bone marrow was assayed by the addition of the marrow supernatant from rats with AIA to control cultures. Bone mineral density was determined by dual x ray absorptiometry. RESULTS–Marrow from AIA rats and that from animals receiving recombinant human interleukin-1 (IL-1) beta for seven days grew significantly fewer FCFU than control marrow. Formation of osteoclast-like cells was increased in bone marrow cultures from rats with AIA, especially when bone marrow cells were cultured in the presence of marrow supernatant. Formation of resorption lacunae on ivory slices was increased in the marrow cultures from rats with AIA, especially from the right (adjuvant inoculated) tibia. AIA rat marrow supernatant promoted osteoclast-like cell formation in control culture, and this was significantly suppressed by an anti-IL-1 antibody. Rats with AIA showed a significant decrease in the bone mineral density of the periarticular regions of the tibia and femur. CONCLUSION–An uncoupled state in bone resorption-formation linkage, possibly mediated through an increase of IL-1 in the bone marrow, may contribute to the development of periarticular osteopenia in inflammatory arthritis.